Hydrochemical Evaluation of Surface and Groundwater in Khan Al-Baghdadi Area, Al- Anbar Province / West of Iraq - Hussien, Sarmad Jamal; Abdulhussein, Firas Mudhafar (Iraqi Journal of Science, 2020)
The hydrochemical study of the surface and groundwater in Khan AL-Baghdadi area included interpretation of physical, chemical and biological properties of 14 wells and 6 surface water samples collected from Euphrates River.. The study covered two periods representing dry and wet periods in October 2018 and April 2019, respectively. The surface water samples were characterized as slightly alkaline, fresh water, excessively mineralized, calcium-chloride type, and hard to very hard class. While the groundwater samples were characterized as slightly alkaline, brackish water, excessively mineralized, calcium-chloride and sodium-chloride type, and hard to very hard class. The assessment of water for irrigation purposes for both water sources in the dry period showed a Sodium Adsorption Ratio (SAR) of no harmful effects, while the Soluble Sodium Percentage (Na%) demonstrated a good irrigation Water Class, except for one well with a permissible irrigation Water Class. While in the wet period, all surface and groundwater samples were of a good irrigation Water Class, except for two wells with permissible irrigation Water Class. In terms of total dissolved solids (TDS) and electrical conductivity (EC), all surface water samples for the two periods were within the permissible limits of irrigation water quality, whereas groundwater samples for the two periods showed unsuitable limits, except for three wells within the permissible limits of irrigation water quality. The microbiological tests showed that all samples of surface and groundwater are classified as clean.